Low Sensitivity of International Classification of Diseases, Tenth Revision Coding for Culture-Confirmed Candidemia Cases in an Active Surveillance System: United States, 2019–2020. (7th September 2022) - Benedict, Kaitlin; Gold, Jeremy A W; Jenkins, Emily N; Roland, Jeremy; Barter, Devra; Czaja, Christopher A; Johnston, Helen; Clogher, Paula; Farley, Monica M; Revis, Andrew; Harrison, Lee H; Tourdot, Laura; et al.
Abstract: We evaluated healthcare facility use of International Classification of Diseases, Tenth Revision (ICD-10) codes for culture-confirmed candidemia cases detected by active public health surveillance during 2019–2020. Most cases (56%) did not receive a candidiasis code, suggesting that studies relying on ICD-10 codes likely underestimate disease burden.